Занимательная Греция: рассказы о древнегреческой культуре (М. Л. Гаспаров) - Гаспаров Михаил Леонович (2014)
Экземпляры: БС (20170211) / Инвентарный номер: РТШ53980 / Сис.шифр: 63.3(0)32 / Авт.знак: Г 22 / ГРНТИ: 03 / ББК: 63.3(0)32